The Factors Related to Food Waste Disposal Behavior of Students in the Dormitory in STIKes Santa Elisabeth Medan: Food Waste Disposal Behavior - Iralomal Oktavia Sitompul; Pane, Jagentar; Simorangkir, Lindawati (STIKes Mandala Waluya Kendari, 2024)
Background: Food waste refers to food that should be consumed but is discarded for specific reasons. Factors contributing to food waste include neglecting the menu, preparing it more than twice a day, the appearance of the meal, and inaccurate perceptions of the food's taste. Reducing food waste can be achieved by valuing food as an essential aspect of human life and managing food consumption effectively. Based on a survey conducted in dormitories, the problem identified is the significant number of leftovers daily, ranging from 4-6 buckets consisting of vegetables, tempeh, and tofu, mainly because the food does not appeal to the students' tastes. The purpose of this study is to identify the factors related to the food waste disposal behavior of students at the STIKes Santa Elisabeth Medan dormitory in 2023. Methods: : A cross-sectional approach combined with correlational research was employed in this investigation. The sample consisted of 84 students living in the dormitory. Instruments used in this study included a Food Waste Questionnaire and Food Scales Questionaire. Data were analyzed using Chi-square to determine the relationship of each independent variable are Food Appearance and Food Taste Factors with the dependent variable is the behavior of throwing food waste.. Results: Results indicated a significant relationship between unattractive food appearance and high food waste, with 90.4% showing high waste and 9.6% showing low waste, confirmed by a Chi-square value of 455a and a p-value of 0.05. Conclusions: The conclusion of this study is that there is a significant relationship between the unattractive appearance of food and the behavior of discarding food waste by dormitory students